Salivary Metabolite Variation After High-Intensity Rowing Training and Potential Biomarker Screening for Exercise-Induced Muscle Damage - Yue Yi; Junjie Ding; Baoguo Wang; Yuxian Li; Liming Wang; Shumin Bo; Qiongqiong Ren; Aiqin Luo (Metabolites)
Background: Exercise-induced muscle damage (EIMD) is the most common health risk in training. So far, EIMD diagnosis predominantly relies on blood biochemical analysis or medical imaging. EIMD prediction by using saliva shows great prospects in public fitness. Methods: A total of 18 participants performed high-intensity rowing training. Blood biochemical indicator and pain analyses indicated EIMD occurrence. Pseudo-targeted metabolomics techniques were utilized to analyze changes in salivary metabolites after exercise. Results: A total of 43 salivary metabolites significantly increased while 31 salivary metabolites significantly decreased after exercise. The upregulated metabolites were related to hormone secretion, antioxidation, and muscle repair. A partial least squares discriminant analysis model was established, and three potential salivary biomarkers for EIMD prediction were screened. The sensitivity and specificity of single biomarkers achieved more than 88.9% and 94.4% in classification of EIMD occurrence, respectively. The accuracy of classification increased to ~100% with multiple metabolites. Conclusion: Salivary metabolites significantly changed after high-intensity rowing training and EIMD occurrence. Some salivary metabolites exhibited similar trends with blood biochemical indicators. Salivary biomarkers have great prospects in EIMD prediction, and better performance was achieved with multiple salivary metabolites.